Vitamin A and retinoids : (Birkhauser Verlag, 2000)
Rapid progress has been made in our understanding of the molecular mechanisms of cell growth and oncogenesis during the past decade. Special attention has been given to the presentation of the frequently neglected close correlation between changes in signal transduction and metabolic pathways during oncogenesis. This book advances the knowledge of mechanisms regulating metabolism and functioning of vitamin A and offers the most recent results of research on the clinical efficiency of retinoids in skin disorders and cancer. The book presents recent findings on the regulation of cell growth in normal and neoplastic tissues by growth factors including hormones, and by the activation and inactivation of oncogenes and tumor suppressor genes, respectively. It also offers a survey of the molecular and cell biochemistry of retinoids. Basic researchers in biochemistry, pharmacology and cell biology as well as clinicians will find this book very informative and up-to-date.